A critical evaluation of the town planning law of Northern Cyprus in line with the European spatial development perspective - Uluçay, Pınar (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2013)
ABSTRACT: The economic, social and political integration of Europe have not only led to the emergence of an extensive body of policies on various sectors aiming to create a more competitive Europe but gradually paved the way for the materialization of spatial planning policies as a tool to coordinate the spatial impacts of the emerging sectoral policies so that the sustainable development of the European Union (EU) can be attained. Although legally comprised no binding rules, the spatial planning policies have managed to trigger major shifts in the planning legislation and practices of several member states through the implementation tools they promoted; and undoubtedly necessitated planning actors develop awareness on this new field. The circumstances expressed above have also become pertinent for the case of this study, Northern Cyprus, where the allocation of EU funds to Turkish Cypriot Community after the entry of Cyprus to the EU in 2004 have not only caused change in the existing planning legislation but also attracted the interest of planning professionals to the concept of European spatial planning for creating sustainable solutions to the current problems arising from the traditional planning system. Built upon the challenging task of the Town Planning Department to initiate reforms in its legislative structure and planning practice in line with the European spatial planning guidelines, the thesis utilizes a combination of descriptive, explanatory and exploratory research approaches to understanding the general field of European spatial planning and the theory of policy making and analysis in a relative context so that a systematic structure for the evaluation of the European Spatial Development Perspective (ESDP) and the key legal document guiding the urban development in the entirety of Northern Cyprus, the Town Planning Law (55/89) can be accomplished. Although the findings of the methodical evaluation confirm that there is a degree of conformity with the ESDP, nonetheless it remains crucial for the Town Planning Law to restructure itself in order to assist the convergence of the existing planning system to European standards. Accordingly, the said document should be reorganized to promote a more participative approach to planning where all stakeholders and major sectors with spatial impacts are incorporated into the process with the utilization of local and national planning tools; and awareness to European planning issues are enhanced with the endorsement of cross-border and transnational planning tools. Keywords: European Spatial Planning System, Urban Policy Analysis, the European Spatial Development Perspective, Town Planning System of Northern Cyprus, the Town Planning Law of Northern Cyprus (55/89) ………………………………………………………………………………………………………………………… OZ: Avrupa Birliği'nin (AB) küresel ekonomi içindeki rekabet edebilirliliğini artırmayı hedefleyen ekonomik, sosyal ve politik entegrasyonu, sektörel politikalara yön verirken, ayni zamanda birbiri ile çelişen sektörel politikaların de hayata geçmesini sağlamıştır. Mekan üzerinde etkileri olduğu anlaşılan bu politik araçların eşgüdümlü olararak ele alınmasının önemine dikkat çeken; ve bunun AB’nin sürdürülebilir gelişimi açısından önemli olduğunu vurgulayan Avrupa mekansal planlama politikaları ise sektörel hedeflerin uyumlaştırılmasını ve entegrasyonunu hedefler. Bu amaç doğrultusunda, Avrupa Komiyonu ve üye ülkelerin girişimleri ile hazırlanan ve mekanı hedef alan stratejik/politik belgelerin, yasal bağlayıcılıkları olmamasına rağmen, yeni ve meşru bilgi kaynakları olmaları dolayısı ile önerdikleri yöntemlerin ve uygulama araçlarının, pekçok üye devletin planlama mevzuatlarında değişimi tetikledikleri bilinmektedir. Bu durum planlama ile ilgili kurum, kuruluş ve aktörlerin yeni politikalar oluşturarak AB düzeyinde de farkındalık geliştirmelerini sağlamıştır. Kıbrıs’ın 2004 yılında AB’ye katılması ile beraber Avrupa Komisyonu’nun Kuzey Kıbrıs’a sağladığı mali yardım; KKTC mevzuatının AB yasalarına uyumlaştırılmasını bir gereklilik haline getirmiştir. Bu çerçevede talep edilen teknik yardım aracılığı ile planlama ile ilgili yasal mevzuatın yeniden yapılandırılması gündeme gelirken, paylaşılan süreçte planlamadan sorumlu profesyonelleri de Avrupa mekansal planlama kavramı ile tanıştırmıştır. Bu çerçeveden bakıldığında Avrupa mekansal planlama yaklaşımı, geleneksel planlama sisteminin bir sonucu olarak ortaya çıkan çeşitli kentsel sorunların çözümlenmesinde yenilikçi bir araç olarak görülmektedir. Tez, bu hedef doğrultusunda Avrupa mekansal planlama yaklaşımına ve mekansal politikaların analiz yöntemlerine göreceli olarak bakmakta; kurguladığı sistematik yöntem aracılığı ile Avrupa Mekansal Gelişim Perspektifi’ni (AMGP) inceleyerek elde edilen bulgular ışığında KKTC’de planlamayı yönlendiren İmar Yasası’nın (55/89) Avrupa Mekansal Planlama ana ilkeleri ışığında nasıl iyileştirilebileceği veya yeniden şekillendirilebileceği konusunda bazı tavsiyelerde bulunulmaktadır. Analiz sonucunda varılan bulgular, İmar Yasası’nın AMGP’ye kısmen uyumlu olduğunu ortaya koymuş olsa da, söz konusu Yasa’nın yenilikçi bir planlama biçimi olarak değerlendirilen Avrupa mekansal planlama yaklaşımını destekleyecek şekilde yeniden düzenlenmesi, hem yasal mevzuatta yapılacak değişiklikleri mümkün kılacak hem de uzun vadede planlama pratiğinin olumlu yönde değişmesini sağlayacaktır. İmar Yasası’nın, tüm ilgili paydaşların ve halkın, ayrıca mekansal etkileri olan birincil sektörlerin sürece katılımlarını artıracak yerel ve ulusal planlama araçlarını; ve Avrupa planlama konularında farkındalığı geliştirecek sınır ötesi ve uluslararası planlama araçlarını meşru kılacak şekilde yeniden düzenlenmesi, Avrupa mekansal planlama sistemine uyum sağlama anlamında önemli bir adım olacaktır. Anahtar Kelimeler: Avrupa Mekansal Planlama Sistemi, Kent Politikaları Analizi, AMGP, Kuzey Kıbrıs Planlama Sistemi ve İmar Yasası (55/89).
Doctor of Philosophy in Architecture. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Architecture, Dept. of Architecture, 2013. Supervisor: Prof. Dr. Ruşen Keleş.
Keywords: Architecture; City planning and Law - Cyprus (Turkish Republic of Northern Cyprus, 1983-)